Diseases in pet degus: a retrospective study in 300 animals - Jekl, V; Hauptman, K; Knotek, Z (The Journal of small animal practice, 2011)
INTRODUCTION: Degus are commonly used as laboratory animals; however, over the past few years, they have become increasingly popular as pets. OBJECTIVES: The aim of this article was to present disease prevalence in 300 pet degus divided in two age groups (under and above two years). METHODS: Medical records of degus (Octodon degus), which were presented to the author's clinic in the period from January 2007 to December 2009, were reviewed. RESULTS: The most common diseases in degus were (1) acquired dental disease (60·0%) with significantly higher prevalence in older animals (P<0.001), (2) skin alopecia due to fur chewing (13·33%) and (3) lens cataracts (13·33%). Other common disorders included traumatic injuries to soft tissues (bite wounds and tail slip), traumatic fractures and dietary diarrhoea. Reproductive disorders were most commonly associated with dystocia and pathological changes in the post-natal period. Only 38 degus in a total of 300 animals were healthy. CLINICAL SIGNIFICANCE: This is the first study to describe the disease prevalence in two age groups of pet degus. The majority of diseases were caused by improper diet, self-mutilation and improper handling; as such client education is necessary to avoid such a high disease prevalence.
Keywords: Female; Prevalence; Rodent Diseases; věkové faktory; retrospektivní studie; Octodon; mužské pohlaví; zvířata; ženské pohlaví; prevalence; nemoci hlodavců; Age Factors; Animals; Animal Husbandry; chov zvířat; Male; Retrospective Studies; Wounds and Injuries; rány a poranění